Land and building tax earnings in Sukabumi sub district of Bandar Lampung - Damayanti Damayanti (Jurnal Ilmiah ESAI, 2014)
Tax on land and building is one the sources of state income from tax sector. This role is more crucial for government in the level of district since the tax policy issued on October 23rd 1993 which regulates that 90% of the state income from this tax is returned to the regional government. However, in the year 2010 there were 12 sub districts which failed to reach the targeted income from this tax, among others is Sukabumi sub district of Bandar Lampung. It can be concluded that the condition was caused by some factors which were : the low performance of the government in this level in collecting the tax ; lack of awareness of the society to pay tax; and lack of law enforcement in tax evasion especially in tax on land building.Keywords: tax on land and building, factors influencing, tax income target, optimizing